Endovascular treatment for distal basilar artery occlusion stroke - Song, Jiaxing; Yu, Zhou; Wang, Jian; Luo, Xiaojun; Du, Jie; Tian, Zhengxuan; Yang, Shunyu; Xie, Weihua; Peng, Yuqi; Mu, Jinlin; Zi, Wenjie; Huang, Shuchun; et al. (Frontiers in Neurology, 2022)
Background: This study aimed to investigate the clinical outcomes of endovascular treatment for distal basilar artery occlusion and compare them with the outcomes of standard medical treatment (SMT) in daily clinical practice. Methods: Patients with distal basilar artery occlusion enrolled in the BASILAR study from January 2014 to May 2019 were included. Differences in clinical outcomes were analyzed by Pearson’s chi–square test and multivariable logistic regression. Endovascular treatment or standard medical treatment with or without intravenous thrombolysis (IVT). Clinical outcomes were evaluated with the modified Rankin Scale (mRS) score at 90–day， the mortality at 90–day and the occurrence of symptomatic intracranial hemorrhage within 48 hours. Results: Among the 267 patients with distal basilar artery occlusion (222 patients in the EVT group and 45 patients in the SMT group), Compared to the SMT group, the EVT group were associated with a favorable outcome (mRS 0-3) (40.1% vs 15.6%; aOR 5.44; 95% CI, 1.68-17.66; P=0.005) and decreased mortality (44.6% vs 71.1%, aOR 0.32, 95% CI, 0.13-0.77; P=0.012). In the EVT group, multivariable analysis showed that initial National Institutes of Health Stroke Scale (NIHSS) score, posterior circulation–Alberta Stroke Program Early CT Score (pc–ASPECTS) were associated with favorable functional outcomes and mortality. Conclusions: Our study suggest that, compared with SMT, EVT is technically feasible and safe for patients with distal basilar artery occlusion.